One-pot green synthesis of highly reduced graphene oxide decorated with silver nanoparticles - Nur Suhaili Abd Aziz,; Muhammad Khairullah Nor Azmi,; Abdul Manaf Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2017)
A one-pot green sonochemical process assisted by ascorbic acid as the reducing agent to produce highly reduced graphene oxide (rGO) decorated with silver nanoparticles (AgNPs) is demonstrated. A complete removal of oxygen-containing group in the GO sheets was confirmed by no observation of the peak corresponds to C-O, C=O and -OH bond. The unexpected decrease of peak intensity corresponds to sp2 hybridized C=C group is explained by a so-called bond polarity effect. The peak observed at ~400 nm seems to show the presence of AgNPs and the red shifting of C=C peak to ~270 nm after the introduction of ascorbic acid indicates the formation of highly reduced GO. The increase of AgNPs size and the crumpled silk-like morphology after the introduction of ascorbic acid also indicate the aggressive reduction of both AgNPs and GO. The increase of ID/IG ratio after the introduction of ascorbic acid seems to indicate the increase of the number of small sp2 domains, the presence of unrepaired defects and the restoration of the sp2 network. This work provides the promising green sonochemical approach by utilizing non-toxic and environmental-friendly reducing agent to produce highly reduced GO decorated with AgNPs for various applications.